A case study on spatial and temporal hydraulic variability in an alpine gravel‐bed stream based on the hydromorphological index of diversity. Issue 4 (17th February 2013) - Gostner, W.; Parasiewicz, P.; Schleiss, A. J.; Blanckaert, Koen; Garcia, Xavier‐François; Steiger, Johannes; Uijttewaal, Wim
ABSTRACT Physical heterogeneity is a major topic in river sciences because it is known to be a key factor for ecological integrity. In this paper, we investigated the hydraulic enviroment in an alpine gravel‐bed stream with an unaltered hydrological regime. The study was based on the hypothesis that spatial and temporal variability are correlated to the morphological template of a stream. Numerical hydrodynamic modelling was conducted at five morphologically contrasting study sites for different discharges chosen from discharge duration curves. On the basis of the resulting hydraulic variables, namely flow velocity and water depth, and of a recently proposed hydromorphological index of diversity, the differences in spatial and temporal variability were analysed by descriptive statistics. Spatial diversity was higher at morphologically natural sites than at sites that were partially or fully regulated by resectioning and bank protection. Conversely, temporal variability in the hydraulic environment was higher at regulated sites where hydraulic variables were subject to fluctuations with each small discharge modification, which is not the case for more impaired sites. Unless higher discharges with bed reshaping activity occur, natural streams are characterized not only by high spatial variability but also by a sustained persistence of aquatic habitats. Therefore, river engineering projects aimed at enhancing habitat heterogeneity should not only focus on a higher spatial variability of the physical environment but also aim for greater persistence of aquatic habitats. Copyright © 2013 John Wiley & Sons, Ltd.